Entry and Exit of Physicians in a two-tiered public/private Health Care System - Martin Gächter; Peter Schwazer; Engelbert Theurl (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2011)
Firm turnover has recently attracted increased interest in economic research. The entry of new firms increases competition and promises efficiency gains. Moreover, changes in the market structure influence productivity growth, because firm entry usually leads to increased innovation. The health care market exhibits important differences as compared to other markets, including various forms of market failure and, as a consequence, extensive market regulation. Thus, the economic effects of entries and exits in health care markets are less obvious. The following paper studies the determinants of entry and exit decisions of physicians in the private sector of the outpatient part of the Austrian health care system. We apply a Poisson panel estimation to a data set of 2,379 local communities and 121 districts in Austria in the time period 2002 - 2008. We are particularly interested in the question how public physicians (GPs/specialists) and their private counterparts influence the entrance and exit of private physicians. We find a significantly negative effect of existing capacities, measured by both private and public physician density of the same specialty, on the entry of new private physicians. On the contrary, we find a significantly positive effect of private GPs on the entry of private specialists. Interestingly, this cooperation/network effect also works in the other direction, as a higher density of private specialists increases the probability of the market entry of private GPs. Based on the results of previous literature, we thus conclude that private physicians establish networks to cooperate in terms of mutual referrals etc. Our estimations for market exits basically confirm the entry results, as higher competitive forces positively influence the market exit of private physicians.
Keywords: I11; I18; L14; 330; Entry; Exit; Health Care; Physician location